Digital Information and Communication Technologies in the Perception of Nursing Professors: Integrative Literature Review - dos Santos, Karen Daniele Rocha; de Fátima Ribeiro Higa, Elza; Lazarini, Carlos Alberto; Garcia, Luis Hilário Tobler; de Oliveira Medeiros, Rodolfo [UNESP] (My University, 2024)
Introduction: The adoption of Digital Information and Communication Technologies (DICT) in higher education nursing courses is increasingly frequent because it propitiates the rupture of didactic paradigms and diversified experiences to professors, thus collaborating to the development of clinical skills and improvement of attitudes, considering the training of critical, self-assured and reflexive professionals. Objective: Analyze what the literature presents about the use of Digital Information and Communication Technologies from the perception of professors of nursing undergraduate courses. Method: Integrative Literature Review (ILR), structured in six stages: Guiding question, establishment of inclusion and exclusion criteria, data collection, categorization and assessment, interpretation, and preparation of the final text. The search was conducted in LILACS, BDENF, IBECS, MEDLINE, ERIC, CUMED, SCOPUS, BINACIS, and Web of Science databases. Results: With the 19 papers included, four categories were structured: Benefits of the use of Digital Information and Communication Technologies in the nursing undergraduate course—highlighting in-person or remote meetings, resignification of learning, interaction, and cooperation of those involved; conditioning factors for the use of Digital Information and Communication Technologies—and showing a teaching environment that is rich in dynamism, interactivity, collaboration, and methodological variation; frailties in teaching praxis with the use of DICTs; and challenges in the implementation of Digital Information and Communication Technologies in the academic environment—highlighting uncertainties and resistances. Conclusions: The use of DICTs generates benefits, indicates the factors that encourage their use, and the frailties and challenges found in professor’s practice in nursing undergraduate courses.
Keywords: Digital technology; Information technology; Nursing education; Nursing professors; Teaching